During Resistance Training the Effect of Ibuprofen on Muscle Hypertrophy Regarding Strength and Soreness. A Population Based Cross-Sectional Study - Rizwana Hussain, Muhammad Umar, Mamoona Shuja, Sehar Khowaja, Sarwat Jabeen, Syed Saim Ali Shah, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Non-steroidal anti-inflammatory medicines (NSAIDs) are frequently used to speed up post-exercise recovery and lessen discomfort and soreness in muscles. There is a concept that Ibuprofen at high doses has been found to prevent the production of muscle proteins following a session of resistance training. Aims and Objectives: To examine the effects of 400 mg/ day dose of ibuprofen on muscular hypertrophy and strength following resistance exercise. Practical Implications: According to the study, using a low dose of ibuprofen (400 mg/day) following resistance exercise may help lessen stiffness and pain in the muscles. This practical application can help those who want to recuperate more quickly after exercising and maintain their training regimen more easily. For best outcomes and general well-being, it's crucial to inform people and encourage a balanced strategy that incorporates medicine with appropriate exercise methods and rest.